G48(P) Wrist-worn devices to improve arm movement in hemiplegic cerebral palsy: participatory design workshops. (25th October 2020) - Brown, R; Pearse, J; Edmonds, G; Nappey, T; Ladha, K; Jackson, D; Guan, Y; Basu, A
Abstract : Background: Hemiplegic Cerebral Palsy causes unilateral weakness and stiffness. Upper limb therapy at effective intensity is not accessible to most. Aim: Determine stakeholder views on design of an approach using wrist-worn devices and software (phone application) incorporating positive feedback and peer support, to encourage use of the affected arm and hand. Method: Five participatory design workshops, incorporating the views of 5 young people (YP) with hemiplegia and 13 typically developing (TD) (8–18 years) plus three parents, six researchers, three occupational therapists, one teacher and two paediatricians. Results: Four themes were noted: Ease/practical issues, Appearance/comfort, Incentives, and Access to participants. Ease/practical issues: Distinguishing between left and right devices proved challenging, so images of differing orientation were added. Concern about teachers' disapproval was resolved by producing an explanatory 'business card' for YP to hand out. Mobile phones are not required in school as the device and app can synchronise later, via Bluetooth. Concerns were addressed, regarding whether devices could gather secure information from arm movement, e.g. PIN numbers. Reassuringly, data is averaged over a minute, rendering this impossible. A parent asked whether GPs could use the data for other purposes (e.g. investigation of tremor) - but this would present challenges. Incentives: Games were a popular incentive, especially those with a competitive element. Inclusion of the game and summarised data showing progress was favoured. Parents were incentivised by this opportunity for their child to receive help and take responsibility for therapy. Appearance/comfort: The devices were programmed to display the time, in response to requests from YP. Wearing two devices was mildly perturbing for older participants as this would be considered unusual, though all were prepared to do it for the project duration. Access to participants: Recruitment to the workshops through advertising and patient groups was challenging; however, in the planned study, we will recruit through the NHS. Conclusion: The participatory design process informed plans for the proof of concept stage of the study, hopefully leading to a product and approach that will be fun, easy to integrate into everyday life, and have the capacity to increase use of the affected arm and hand.